2013
DOI: 10.1007/s10198-013-0478-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of injectable disease-modifying therapies for the treatment of relapsing forms of multiple sclerosis in Spain

Abstract: In our cost-effectiveness analysis of first-line injectable DMTs in Spain, we found IM IFNβ-1a to be more cost-effective than SC IFNβ-1a, IFNβ-1b or GA. Sensitivity analyses confirmed the robustness of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 32 publications
0
33
1
Order By: Relevance
“…On the basis of title and abstract, 1168 records were excluded and the remaining 225 records were included for full-text screening. A further 213 articles were excluded at the full-text stage (see Appendix 7 for a list of excluded studies with reasons), leaving 10 studies 154,[264][265][266][267][268][269][270][271][272] that included a decision-analytic model used to estimate the cost-effectiveness of DMTs for treating people with RRMS. …”
Section: Results Of the Searches For Relapsing-remitting Multiple Sclmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of title and abstract, 1168 records were excluded and the remaining 225 records were included for full-text screening. A further 213 articles were excluded at the full-text stage (see Appendix 7 for a list of excluded studies with reasons), leaving 10 studies 154,[264][265][266][267][268][269][270][271][272] that included a decision-analytic model used to estimate the cost-effectiveness of DMTs for treating people with RRMS. …”
Section: Results Of the Searches For Relapsing-remitting Multiple Sclmentioning
confidence: 99%
“…Dembek et al 270 Dembek et al 270 undertook a cost-effectiveness analysis to estimate the incremental costs and benefits of injectable DMTs in comparison with BSC in Spain. They compared three different regimens of IFN and GA.…”
Section: Imani and Golestani 269mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The seven studies finally selected [10][11][12][13][14][15][16] came from only four countries (Germany, Italy, Spain, and Sweden) ( Table 1); three focused on clinically isolated syndrome (CIS) 2 (comparing DMD vs. 'do nothing' or early vs. delayed regimens of the same DMD) and the other four on RRMS patients (comparing the two IFNbs and GA). Three studies included a cost-utility analysis, two a cost-effectiveness analysis, and the others both.…”
Section: Economic Evaluations In the European Unionmentioning
confidence: 99%
“…, using the utility index (QALY) to compare these two medicines, indicated that intramuscular Interferon beta1a (Avonex) was more cost -effective than subcutaneous Interferon beta -1 (Rebif) (21,24,28,45).…”
mentioning
confidence: 99%